Evaluation of Scopoletin from Penicillium janthinellum Snef1650 for the Control of Heterodera glycines in Soybean - Jichen Yan (MDPI AG, 2021)
Soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is responsible for causing a major soybean disease globally. The fungal strain Penicillium janthinellum Snef1650 was evaluated against H. glycines. However, the effective determinants of the P. janthinellum strain are unknown. By performing pot experiments, a functioning compound was isolated from P. janthinellum Snef1650 through organic solvent extraction, semi-preparative HPLC, Sephadex LH-20 column chromatography, and silica gel column chromatography, and the isolated compound was identified to be scopoletin through 1H NMR, 13C NMR, and HPLC–MS. The pot experiments indicated that the treatment of soybean seeds with scopoletin drastically reduced the SCN population. The field experiments performed in 2017 and 2018 revealed that scopoletin decreased over 43.7% juveniles in the roots and over 61.55% cysts in the soil. Scopoletin treatment also promoted soybean growth and improved its yield, with an increase in plot yield by >5.33%. Scopoletin obtained from P. janthinellum Snef1650 could be used as an anti-H. glycines biocontrol agent.